Gestural minds unfolding: on becoming fully equipped and fully licensed gestural signers - Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2022)
The article is a theoretical framework on becoming fully equipped and licensed gestural signer. The establishment of a complete gestural mind in every single human individual is assumed to follow a phasing procedure and these phases are explained in the article.